PENGARUH PERSEPSI HARGA, DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION DAN KEPUASAN KONSUMEN DI APLIKASI SHOPEE (Studi Kasus Pada Mahasiswa FEB Universitas Riau) - Asnita Yuli Nova; Taufiqurrahman Taufiqurrahman; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to analyze the effect of the Perceived Price and Perceived Easeof Transactions on the Purchase Decision of Fashion Products and ConsumerSatisfaction at Shopee Aplication. This research was conducted on all activeundergraduate students of the Faculty of Economics and Business, University ofRiau who use the Shopee market place in shopping for unknown fashion products.This research consists of four variables : Purchase Decision (Y1), ConsumerSatisfaction (Y2), Perception of Transaction Ease (X2), and Perception of Price(X1). This research was conducted using a sample of 130 respondents. This studyuses a purposive sampling method, namely the determination of the sample basedon respondents who have certain criteria. Meanwhile, in terms of data analysis,this study uses the Path Analysis method with the help of SPSS (Statistical Packageof Social Science) version 25. Based on the hypothesis test carried out, the resultsshow that Perception of Transaction Ease has a Positive and Significant Effect onPurchase Decisions, Price Perception has a Positive Effect and Significant toConsumer Satisfaction through Purchase Decisions, Perception of Ease ofTransactions has a positive and significant effect on Consumer Satisfaction throughPurchase Decisions, Purchase Decisions have a positive and significant effect onConsumer Satisfaction. Keywords: Perception of Price, Perception of Transaction Ease, PurchaseDecision, Consumer Satisfaction.